A Problematic Issue Of Child Marriage In The Sea Tribe (Suku Laut) In Lipan Island at Lingga Regency - Winsherly Tan (Pattimura Law Journal, 2022)
Child marriage is one of the issues that occurred in Indonesia, especially in the Sea Tribe (Suku Laut) community in Lipan Island, Lingga Regency of the Riau Islands Province. Indonesia has a regulation that governs child protection and marriage. This study aimed at, firstly, analyzing the effectiveness of implementing laws on marriage in the Sea Tribe people in Lipan Island. Secondly, it aimed at analysing the impacts of the child marriage practices. The method used in this study was an empirical legal research. The source of data was derived from primary and secondary data. Two (2) legal theories were adopted to analyse the research problems were the Legal Effectiveness Theory by Soerjono Soekanto and the Theory of Legal Protection by Muchsin. The result showed that the implementation of laws on marriage was not effective. The impact caused by a child marriage is the violation of children’s rights in the health and education sectors. Therefore, a revision against Law Number 16 of 2019 concerning Marriage is required, in addition to the improvement of education educational quality for Sea Tribe people in Lipan Island.